Cytokine and reactivity profiles in SLE patients following anti-CD19 CART therapy - Nunez, Daniel; Patel, Darshil; Volkov, Jenell; Wong, Steven; Vorndran, Zachary; Müller, Fabian; Aigner, Michael; Völkl, Simon; Mackensen, Andreas; Schett, Georg; Basu, Samik (Molecular Therapy, 2023)
Chimeric antigen receptor (CAR) T cells targeting CD19+ B cells have demonstrated efficacy in refractory systemic lupus erythematosus (SLE). Although initial clinical data suggest that anti-CD19 CAR T cell therapy is well tolerated and highly effective, the immunologic consequences of CAR T cell therapy in SLE patients remain unclear. We profiled serum in six refractory SLE patients prior to and 3 months following CAR T cell infusion. Three months post T cell infusion, the inflammatory cytokines IL-6 and TNFα decreased in patient sera. This was accompanied by elevations in serum IL-7 and BAFF. Furthermore, SLE-associated antibodies dropped profoundly in five of six patients. Last, consistent with other reports of CD19 CAR T therapy in B cell malignancies, we were able to show marginal impact of anti-CD19 CART therapy on pre-existing humoral immune responses in SLE patients. Together, these results provide insights into the mechanisms of efficacy of anti-CD19 CAR T cell therapy in SLE.
CRIS-Team Scopus Importer:2023-09-29
Keywords: antibodies; autoimmune disease; CAR; chimeric antigen receptor T cell; cytokines; SLE; systemic lupus erythematous; vaccines